Evolution of scientific production on the Efficient Market: Bibliometric study - Moraes, Alexandra Kelly de; Furtini, Andressa Aparecida Santana; Prado, José Willer do; Castro Junior, Luiz Gonzaga de; Ceretta, Paulo Sergio (Contextus - Revista Contemporânea de Economia e Gestão, 2024)
Contextualization: The text highlights the importance of Market Efficiency in the dynamic and complex market environment, which has been widely studied and analyzed. The approach to this topic arouses interest in academia and has been the subject of several studies. Objective: The study aims to map scientific production related to the concept of Efficient Market, analyzing the evolution of academic work and research on the topic over time. Method: The research adopts a descriptive approach with a quantitative focus and bibliometric analysis to measure scientific productivity indices on a specific topic. 478 relevant articles were identified in the Web of Science and Scopus databases from 1977 to 2023. The EndNote and Bibliometrix R software were used for analysis, followed by the creation of statistical tables and graphs for presentation in the biblioshiny and VOSviewer software. Results: Data analysis revealed a constant increase in publications in the field of finance related to the topic, with emphasis on specific journals. Journal affiliations were mainly concentrated in the regions of America, Europe and Asia, in areas such as statistics, economics, business and management. Important references and topics covered included market efficiency, behavioral finance and stock market efficiency. Eugene Fama was highlighted as the most influential author. As for future trends, areas such as market efficiency analysis, risk management and predictability in periods of global conflicts have been identified, requiring complex and innovative methods. Conclusions: These results contribute to expanding knowledge and understanding about market efficiency, encouraging the search for innovative and complex approaches to further advance this field of study.